Efisiensi Energi pada Bangunan Cerdas (Smart Building) Berbasis Teknologi Sensor dan Otomasi - Halim Nugraha (Jurnal Sains dan Teknologi Indonesia, 2025)
This study discusses the implementation of smart building technology with a focus on energy efficiency through the integration of sensors and automation systems. The research highlights how Internet of Things (IoT)-based devices, sensor networks, and automated control systems can optimize energy use in buildings without compromising occupant comfort. Data were collected from various literature sources and case studies that examined the role of lighting control, HVAC systems, renewable energy integration, and real-time monitoring in reducing energy consumption. Findings show that sensor-based smart building systems are capable of reducing electricity use by up to 30%, while improving indoor environmental quality and operational efficiency. Furthermore, automation allows predictive energy management by adjusting energy loads according to real-time occupancy and environmental conditions. The study concludes that smart buildings represent a strategic solution to support sustainability goals and energy conservation policies. Recommendations are made for future applications of artificial intelligence and advanced IoT integration to further optimize building energy efficiency.